Access to financing and firm growth - Rahaman, Mohammad M. (Journal of Banking & Finance, 2011)
Why do some firms grow faster than others? Although various observed and unobserved aspects of firms have been suggested as potential drivers of firm heterogeneity, economists disagree sharply on the role of financial structure in influencing firm growth. In this paper, I use a sample of quoted and unquoted firms to show that the effect of financial structure on firm growth is statistically significant and quantitatively important. In the presence of external financing constraints, firms rely more on internal funds to finance growth, but the effect of internal financing on firm growth decreases with an increase in the firm’s access to an external bank credit facility. As the external financing constraint is alleviated, the firm relies less on internal funds and switches to external financing as the primary source of financing for its growth. This pattern of transition between internal and external financing is particularly pronounced in small unquoted firms (conditional on their survival). These results suggest a real effect of financial structure on growth via the channel of an external financing constraint.